High power impulse magnetron sputtering deposited virucide and antibacterial CrN-Cu films and the durability of the antimicrobial activity - Santiago Domínguez-Meister; Janire Mediavilla; Anastasia Dianova; Noelia Álvarez; Sara Insausti; Edurne Rujas; Jose L. Nieva; Marta Brizuela; Iñigo Braceras (Heliyon)
Surfaces loaded with microbes can contribute to the propagation of a wide variety of pathogens. In this work, the antimicrobial potential of a hard coating (CrN) doped with different proportions of a biocide element (copper) has been studied. The coatings have been deposited by reactive high power impulse magnetron sputtering (HiPIMS) technology, on stainless steel and glass, materials used profusely in high human traffic environments. The microstructural and mechanical properties of the coatings have been evaluated, their antiviral (VSV-G) and antibacterial (S. Aureus) activities, and the durability of the antimicrobial activity, simulating tribologically two years of standard cleaning processes.It has been found that adding Cu to CrN caused some reduction in the coating hardness and Young's modulus, but an increase in the coating adhesion. The effect on surface wettability depended on the Cu content, which caused a reduction for low Cu values (1.1 and 4.4 at. %), but and increase for larger values (11.5 % at. %). All in all, the CrN-Cu coatings studied showed both antiviral and antimicrobial activity, even for low Cu content (1.1 % at. %). The antimicrobial activity actually rose when the surfaces were subjected to repeated cleaning processes, indication of the robust durability in relevant practical environments.